Small-vessel occlusion versus large-artery atherosclerotic strokes in diabetics: Patient characteristics, outcomes, and predictors of stroke mechanism. (June 2016) - Ntaios, G; Milionis, H; Vemmos, K; Makaritsis, K; Ferrari, J; Strbian, D; Curtze, S; Tatlisumak, T; Michel, P; Papavasileiou, V
Introduction: Diabetes mellitus exerts a detrimental effect on cerebral vasculature affecting both macrovasculature and microvasculature. However, although ischaemic stroke is typically included among macrovascular diabetic complications, it is frequently omitted from microvascular diabetic complications. We aimed to compare the proportion of large-artery atherosclerotic and small-vessel occlusion strokes among diabetic stroke patients, explore their differences and outcomes, and assess potential mechanisms which may determine why some diabetic patients suffer large-artery atherosclerotic stroke whereas others suffer small-vessel occlusion stroke. Methods: We pooled data of diabetic patients from four prospective ischaemic stroke registries (Acute Stroke Registry and Analysis of Lausanne (ASTRAL), Athens, Austrian, and Helsinki Stroke Thrombolysis Registries). Stroke severity and prognosis were assessed with National Institutes of Health Stroke Scale (NIHSS) and ASTRAL scores, respectively; functional outcome with three-month modified Rankin score (0–2 considered as favourable outcome). Logistic-regression analysis identified independent predictors of large-artery atherosclerotic stroke. Results: Among 5412 patients, 1069 (19.8%) were diabetics; of them, 232 (21.7%) had large-artery atherosclerotic and 205 (19.2%) small-vessel occlusion strokes. Large-artery atherosclerotic stroke had higher severity than small-vessel occlusion stroke (median NIHSS: 6 vs. 3, p  < 0.001), worse prognosis (median ASTRAL score: 23 vs. 19, p  < 0.001), and worse three-month outcome (60.3% vs. 83.4% with favourable outcome, p  < 0.001). In logistic-regression analysis, peripheral artery disease (odds ratio: 4.013, 95% confidence interval: 1.667–9.665, p  < 0.01) and smoking (odds ratio: 1.706, 95% confidence interval: 1.087–2.675, p  < 0.05) were independently associated with large-artery atherosclerotic strokes. Conclusion: In the diabetic stroke population, small-vessel occlusion and large-artery atherosclerotic strokes occur with similar frequency. Large-artery atherosclerotic strokes are more severe and have worse outcome than small-vessel occlusion strokes. The presence of peripheral artery disease and smoking independently predicted large-artery atherosclerotic stroke.